2018
DOI: 10.3390/molecules23071752
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glycation, Carbonyl Trapping and Anti-inflammatory Activities of Chrysin Derivatives

Abstract: The aim of this study was searching anti-glycation, carbonyl trapping and anti-inflammatory activities of chrysin derivatives. The inhibitory effect of chrysin on advanced glycation end-products (AGEs) was investigated by trapping methylglyoxal (MGO), and MGO-conjugated adducts of chrysin were analyzed using LC-MS/MS. The mono- or di-MGO-conjugated adducts of chrysin were present at 63.86 and 29.69% upon 48 h of incubation at a chrysin:MGO ratio of 1:10. The MGO adducted positions on chrysin were at carbon 6 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
2
22
0
1
Order By: Relevance
“…Indeed, numerous investigations have determined that meta-dihydroxyl substituted aromatic nucleus constitutes the main site of scavenging action of flavonoids. Such patterns have been shown to generate nucleophilic site between to two phenolic groups that can be attacked by the electrophilic aldehyde group of MGO [37]. In line with this, structural analyses of MGO adducts of several common flavonoid derivatives including quercetin, apigenin and genistein have confirmed that positions 6 and 8 of their A ring were the major active sites for scavenging α-dicarbonyl compounds.…”
Section: Mgo Spiking Experiments For Detection Of Main Dicarbonyl Tramentioning
confidence: 69%
“…Indeed, numerous investigations have determined that meta-dihydroxyl substituted aromatic nucleus constitutes the main site of scavenging action of flavonoids. Such patterns have been shown to generate nucleophilic site between to two phenolic groups that can be attacked by the electrophilic aldehyde group of MGO [37]. In line with this, structural analyses of MGO adducts of several common flavonoid derivatives including quercetin, apigenin and genistein have confirmed that positions 6 and 8 of their A ring were the major active sites for scavenging α-dicarbonyl compounds.…”
Section: Mgo Spiking Experiments For Detection Of Main Dicarbonyl Tramentioning
confidence: 69%
“…As active compounds widely distributed in foods, dietary flavonoids have shown inhibitory effects on formation of AGEs [10][11][12]. Moreover, they are identified as inhibitors of many human digestive enzymes, which makes them drug candidates for diabetes mellitus [13].…”
Section: Introductionmentioning
confidence: 99%
“…Chrysin (5,7-dihydroxyflavone) is a flavonoid presents at high levels in propolis and honey [57]. It has a wide range of pharmacological properties, mainly antioxidant [58], anticancer [59], and anti-inflammatory [60]. It has been shown that chrysin, orally supplemented at 50 mg kg −1 day −1 , for 2 months, significantly increased the testicular level of glutathione as well as the activity of the antioxidant enzymes (catalase, glutathione peroxidase, and superoxide dismutase) [61].…”
Section: Main Textmentioning
confidence: 99%